Evaluation of breast cancer screening indicators in the female population using the National Health System, Brazil, 2018-2019: a descriptive study - Jeane Tomazelli; Maria Beatriz Kneipp Dias; Caroline Madalena Ribeiro; Mônica de Assis; Maria Asunción Sole Pla; Ellyete de Oliveira Canella; Arn Migowski (Ministério da Saúde do Brasil, 2023)
Abstract Objetive: to analyze breast cancer screening monitoring indicators in the female population using the Brazilian National Health System, from 2018 to 2019. Methods: this was a descriptive study based on Cancer Information System (SISCAN) data; screening indicators were calculated following deterministic linkage of the mammography and histopathology databases. Results: in 2018, 807,430 women aged 50 to 69 years were screened for breast cancer, 91% of whom had a benign result, 1.8% probably benign, 6.7% inconclusive results and 0.5% results suggestive of cancer; the positive mammogram rate was 9.0%; biopsy was estimated to be indicated for 1.6% of the women, 33.9% of whom had a malignant result, and the cancer confirmation rate was 5.4 per 1,000 women. Conclusion: high benign lesion loss to follow-up was identified; the positive mammogram rate was lower than the international parameter, but the cancer detection rate was adequate and the percentage of inconclusive mammograms was acceptable.